MODELING OF DYNAMICS OF TEMPERATURE CHANGING IN CASTING AND MOLD AT VARIATION OF DIFFERENT THERMOPHYSICAL CHARACTERISTICS OF CHILL COVERINGS - A. N. Chichko; L. V. Markov (Литьë и металлургия)
Serious enough problem in casting under pressure is presence in a completed part of gas impurities. Such defect limits the possibility of application of this method for production of own parts. The article introduces the decision of problem of porosity owing to use of modem decisions laid at the equipment design stage.